Strategies for avoiding asymmetric information in construction project management - Schieg, Martin (Journal of Business Economics and Management, 2008)
A construction project is characterized by a high number of project participants and a multitude of contract relations. The Principal Agent Theory deals with the design of contracts, especially with respect to asymmetric information. Asymmetric distribution of information in co‐operations can have effects before as well as after closing a contract. In construction project management therefore attention has to be paid to where information imbalances occur. Several methods are known with which one can cope with the resulting problems but which in turn cause costs.First published online: 14 Oct 2010